Trends in Serosorting and the Association With HIV/STI Risk Over Time Among Men Who Have Sex With Men. (1st June 2016) - Khosropour, Christine M.; Dombrowski, Julia C.; Swanson, Fred; Kerani, Roxanne P.; Katz, David A.; Barbee, Lindley A.; Hughes, James P.; Manhart, Lisa E.; Golden, Matthew R.
Abstract : Background: Serosorting among men who have sex with men (MSM) is common, but recent data to describe trends in serosorting are limited. How serosorting affects population-level trends in HIV and other sexually transmitted infection (STI) risk is largely unknown. Methods: We collected data as part of routine care from MSM attending a sexually transmitted disease clinic (2002–2013) and a community-based HIV/sexually transmitted disease testing center (2004–2013) in Seattle, WA. MSM were asked about condom use with HIV-positive, HIV-negative, and unknown-status partners in the prior 12 months. We classified behaviors into 4 mutually exclusive categories: no anal intercourse (AI); consistent condom use (always used condoms for AI); serosorting [condom-less anal intercourse (CAI) only with HIV-concordant partners]; and nonconcordant CAI (CAI with HIV-discordant/unknown-status partners; NCCAI). Results: Behavioral data were complete for 49, 912 clinic visits. Serosorting increased significantly among both HIV-positive and HIV-negative men over the study period. This increase in serosorting was concurrent with a decrease in NCCAI among HIV-negative MSM, but a decrease in consistent condom use among HIV-positive MSM. Adjusting for time since last negative HIV test, the risk of testing HIV positive during the study period decreased among MSM who reported NCCAI (7.1%–2.8%; P = 0.02), serosorting (2.4%–1.3%; P = 0.17), and no CAI (1.5%–0.7%; P = 0.01). Serosorting was associated with a 47% lower risk of testing HIV positive compared with NCCAI (adjusted prevalence ratio = 0.53; 95% confidence interval: 0.45 to 0.62). Conclusions: Between 2002 and 2013, serosorting increased and NCCAI decreased among Seattle MSM. These changes paralleled a decline in HIV test positivity among MSM. Abstract : Supplemental Digital Content is Available in the Text.